‘Speak, Hannah, and Do Not be Silent’: Pseudo-Philo's Deconstruction of Violence in Liber Antiquitatum Biblicarum 50–51 - Lappenga, Benjamin J. (Journal for the study of the pseudepigrapha, 2015)
This article argues that the movement from Hannah's silent prayer in Liber Antiquitatum Biblicarum 50.5 (‘Hannah did not want to pray out loud’), to her bold declaration in 51.5 (‘I will speak my words openly’), interrupts a narrative trajectory involving violent zeal in Pseudo-Philo's rewritten biblical narrative. Throughout the narrative, the prayers of key individuals for God's merciful action on behalf of the people are rendered efficacious by acts of zeal (zelus) that are both public and violent (47.1-3). By contrast, Hannah's act of silent prayer (framed as ‘zeal’ in 50.5) is accepted as the accompanying act for the people's prayer (51.2). This vicarious action helps explain Hannah's expanded role as paradigmatic of all Israel in Liber Antiquitatum Biblicarum and serves to deconstruct the notion that acceptable zeal from Israel's leaders must be manifested with violence.